Marketing Strategy Suggestion of the Commway Program in Bank Commonwealth (The Indonesian Journal of Business Administration, 2013)
The issue with Bank Commonwealth is its brand. To overcome this, the company had run a program named Commway. However, the program only generated a low increase of brand improvement. The purpose of this study was to identify the brand condition of Bank Commonwealth and the solutions to improve its brand effectively by finding out the customer’s perception. In these matters, the management should make improvement regarding the marketing program. The qualitative research methodologies are used in this study. The qualitative research data is acquired by questionnaires. 130 questionnaires were given to Bank Commonwealth customers in Bandung, varying in backgrounds. With 100% respond rate, all of them were responded. The data then would be analyzed using the Importance-Performance Analysis (IPA). The result revealed that people were not well informed with the Bank Commonwealth and its program. The correspondents mentioned that the program is considered to be not special. The author recommends that management within Bank Commonwealth reevaluate their practices and started from introducing their company. It is recommended that Bank Commonwealth conducts efforts with synergized marketing strategy which is more relevant to the company situation and its need. The marketing strategy required by Bank Commonwealth should include broad audience and show something edgy and memorable, focusing in captivating the target’s attention. Key Words: Bank Commonwealth, Importance-Performance Analysis (IPA), and Brand